2020
DOI: 10.1101/2020.01.20.912709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connectomics analysis reveals first, second, and third order thermosensory and hygrosensory neurons in the adultDrosophilabrain

Abstract: HIGHLIGHTS• Two novel thermo/hygrosensory glomeruli in the fly antennal lobe • First complete set of thermosensory and hygrosensory projection neurons • First connectome for a thermosensory centre, the lateral accessory calyx • Novel third order neurons, including a link to the circadian clock SUMMARY (250):Animals exhibit innate and learned preferences for temperature and humidity -conditions critical for their survival and reproduction. Here, we leveraged a whole adult brain electron microscopy volume to stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We acquire the majority of neurotransmitter to neuron assignments used for training and evaluation from published reconstructions in the full adult fly brain (FAFB) dataset (Bates et al, 2020;Dolan et al, 2018;Felsenberg et al, 2018;Frechter et al, 2019;Huoviala et al, 2018;Dolan et al, 2019;Marin et al, 2020;Sayin et al, 2019;Turner-Evans et al, 2019;Zheng et al, 2018), as well as unpublished but identified neuron reconstructions offered by the FAFB community (see acknowledgements). In these studies, the authors had already linked some of their reconstructed cell types to immunohistochemical data (Aso et al, 2014;Bräcker et al, 2013;Busch et al, 2009;Davis et al, 2018;Dolan et al, 2019;Ito et al, 2013;Lai et al, 2008;Okada et al, 2009;Shinomiya et al, 2015;Tanaka et al, 2012;Wilson and Laurent, 2005).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…We acquire the majority of neurotransmitter to neuron assignments used for training and evaluation from published reconstructions in the full adult fly brain (FAFB) dataset (Bates et al, 2020;Dolan et al, 2018;Felsenberg et al, 2018;Frechter et al, 2019;Huoviala et al, 2018;Dolan et al, 2019;Marin et al, 2020;Sayin et al, 2019;Turner-Evans et al, 2019;Zheng et al, 2018), as well as unpublished but identified neuron reconstructions offered by the FAFB community (see acknowledgements). In these studies, the authors had already linked some of their reconstructed cell types to immunohistochemical data (Aso et al, 2014;Bräcker et al, 2013;Busch et al, 2009;Davis et al, 2018;Dolan et al, 2019;Ito et al, 2013;Lai et al, 2008;Okada et al, 2009;Shinomiya et al, 2015;Tanaka et al, 2012;Wilson and Laurent, 2005).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…We began by asking if the connectivity of the CSDn to individual PNs differs across the AL and LH as both the CSDn and PNs span both brain regions. Previously published PN reconstructions [25, 50, 67] were grouped into three subtypes based on whether they were uniglomerular (uPN) or multiglomerular (mPN), and the AL tract along which the mPNs project, either mALT or mlALT [50]. In addition to the AL tract along which they project, mPNs functionally differ from each other in terms of the transmitter they express with mALT mPNs being cholinergic and mlALT mPNs being GABAergic [50, 6870].…”
Section: Resultsmentioning
confidence: 99%
“…Preferential connectivity of JONs within a particular subpopulation has also been shown with the JO-A and -B neurons (Kim et al, 2020). This type of connectivity among sensory neurons is an emerging theme that is increasingly being described in sensory neurons across modalities (Horne et al, 2018;Marin et al, 2020;Miroschnikow et al, 2018;Tobin et al, 2017). However, the functional significance of this type of connectivity remains unclear.…”
Section: Jon Axons Make Synaptic Connections With Each Othermentioning
confidence: 96%
“…The algorithm would occasionally create false splits. Therefore, the tracer resolved these false splits by manually assembling the fragments as previously described (Marin et al, 2020). This approach enabled us to semi-automatically annotate the major branches of each neuron, but not the fine branches and synaptic sites.…”
Section: Neural Circuit Reconstructions From An Em Volumementioning
confidence: 99%